Characterization of airborne particles emitted by an electrically heated tobacco smoking system. (September 2018) - Pacitto, A.; Stabile, L.; Scungio, M.; Rizza, V.; Buonanno, G.
Abstract: Smoking activities were recognized as a main risk factor for population. Indeed, mainstream smoke aerosol is directly inhaled by smokers then delivering harmful compounds in the deepest regions of the lung. In order to reduce the potential risk of smoking, different nicotine delivery products have been recently developed. The latest device released is an electrically heated tobacco system (iQOS ®, Philip Morris) which is able to warm the tobacco with no combustion. In the present paper a dimensional and volatility characterization of iQOS-generated particles was performed through particle number concentration and distribution measurements in the mainstream aerosol. The experimental analysis was carried out through a condensation particle counter, a fast mobility particle sizer and a thermo-dilution sampling system allowing aerosol samplings at different temperatures. Estimates of the particle surface area dose received by smokers were also carried out on the basis of measured data and typical smoking patterns. The particle number concentrations in the mainstream aerosols resulted lower than 1 × 10 8 part. cm −3 with particle number distribution modes of about 100 nm. Nonetheless, the volatility analysis showed the high amount of volatile fraction of iQOS-generated particles, indeed, samplings performed at 300 °C confirmed a significant particle shrinking phenomena (modes of about 20 nm). Anyway, the particle number concentration does not statistically decrease at higher sampling temperatures, then showing that a non-volatile fraction is always presents in the emitted particles. The dose received by smokers in terms of non-volatile amount of particle surface area was equal to 1–2 mm 2 per puff, i.e. up to 4-fold larger than that received by electronic cigarette vapers. Graphical abstract: Image 1 Highlights: Measurements of particle number and surface area concentrations and distributions. Particle number concentrations in the mainstream aerosols were <1 × 10 8 part. cm −3 . Evaluation of the volatile and non-volatile fraction of the particles emitted. The particle number distribution mode in the mainstream aerosol was about 100 nm. The particle number distribution mode of the non-volatile fraction was about 20 nm. Abstract : Dimensional and volatility analysis of the iQOS-generated particles allowed to evaluate the non-volatile particle surface area dose received by iQOS smokers: it resulted higher than that received by electronic cigarette vapers.